Chemically Tuned p‐ and n‐Type WSe2 Monolayers with High Carrier Mobility for Advanced Electronics. Issue 42 (2nd September 2019) - Ji, Hyun Goo; Solís‐Fernández, Pablo; Yoshimura, Daisuke; Maruyama, Mina; Endo, Takahiko; Miyata, Yasumitsu; Okada, Susumu; Ago, Hiroki
Abstract: Monolayers of transition metal dichalcogenides (TMDCs) have attracted a great interest for post‐silicon electronics and photonics due to their high carrier mobility, tunable bandgap, and atom‐thick 2D structure. With the analogy to conventional silicon electronics, establishing a method to convert TMDC to p‐ and n‐type semiconductors is essential for various device applications, such as complementary metal‐oxide‐semiconductor (CMOS) circuits and photovoltaics. Here, a successful control of the electrical polarity of monolayer WSe2 is demonstrated by chemical doping. Two different molecules, 4‐nitrobenzenediazonium tetrafluoroborate and diethylenetriamine, are utilized to convert ambipolar WSe2 field‐effect transistors (FETs) to p‐ and n‐type, respectively. Moreover, the chemically doped WSe2 show increased effective carrier mobilities of 82 and 25 cm 2 V −1 s −1 for holes and electrons, respectively, which are much higher than those of the pristine WSe2 . The doping effects are studied by photoluminescence, Raman, X‐ray photoelectron spectroscopy, and density functional theory. Chemically tuned WSe2 FETs are integrated into CMOS inverters, exhibiting extremely low power consumption (≈ 0.17 nW). Furthermore, a p‐n junction within single WSe2 grain is realized via spatially controlled chemical doping. The chemical doping method for controlling the transport properties of WSe2 will contribute to the development of TMDC‐based advanced electronics. Abstract : Selective tuning of ambipolar WSe2 monolayer to p‐ and n‐type semiconductors by chemical doping is demonstrated. The chemical doping not only allows to control over the main charge carriers, but also increases the carrier mobility of the WSe2 significantly. Furthermore, a complementary metal‐oxide‐semiconductor inverter and an in‐plane p–n junction with superior performance are successfully fabricated by integrating the chemically doped WSe2 .